A comparative study of energy detector performance under AWGN and fading channels - Mohamoud, Mohamoud Ali; Elsheikh, Elsheikh Mohamed Ahmed; Habaebi, Mohamed Hadi (IEEE, 2017)
Cognitive Radio (CR) is an intelligent system for opportunistically accessing the idle resources and a solution for spectrum resources scarcity. The main purpose of this article is to analyze the performance of Energy Detection under Nakagami and Rayleigh fading channels and compare it with the case of when there is only AWGN. Probability of detection and probability of false alarm are used to characterize the performance of the energy detector under different received SNR. It was found that energy detection has better detection performance when there is only noise and this performance deteriorates with the introduction of Nakgami fading. The worst performance was in the case of Rayleigh fading. This clearly shows that the performance of the energy detector is worse in fading channels and further deteriorates with the severity of the fading. Keywords—Cognitive radio, Energy Detection, AWGN, Nakagami fading, Rayleigh fading